Altered Function and Connectivity of the Medial Frontal Cortex in Pediatric Obsessive-Compulsive Disorder - Fitzgerald, Kate Dimond; Stern, Emily R.; Angstadt, Mike; Nicholson-Muth, Karen C.; Maynor, McKenzie R.; Welsh, Robert C.; Hanna, Gregory L.; Taylor, Stephan F. (Biological psychiatry (1969), 2010)
Exaggerated concern for correct performance has been linked to hyperactivity of the medial frontal cortex (MFC) in adult obsessive-compulsive disorder (OCD), but the role of the MFC during the early course of illness remains poorly understood. We tested whether hyperactive MFC-based performance monitoring function relates to altered MFC connectivity within task control and default mode networks in pediatric patients. Eighteen pairs of OCD and matched healthy youth underwent functional magnetic resonance imaging during performance monitoring and at rest. Task-related hyperactivations in the posterior and ventral MFC were used as seeds for connectivity analyses during task and resting state. In posterior MFC, patients showed greater activation of dorsal anterior cingulate cortex (dACC) than control subjects, with greater activation predicting worse performance. In ventral MFC, control subjects exhibited deactivation, whereas patients activated this region. Compared with control subjects, patients showed increased dACC-ventral MFC connectivity during task and decreased dACC-right anterior operculum and ventral MFC-posterior cingulate connectivity during rest. Excessive activation and increased interactions of posterior and ventral MFC during performance monitoring may combine with reduced resting state connectivity of these regions within networks for task control and default mode to reflect early markers of OCD. Alteration of reciprocal interactions between these networks could potentiate the intrusion of ventral MFC-based affectively laden, self-referential thoughts, while disrupting posterior MFC-based performance-monitoring function in young patients.